Properties of treated recycled aggregates and its influence on concrete strength characteristics. (15th May 2016) - Saravanakumar, P.; Abhiram, K.; Manoj, B.
Highlights: The surface treatment by presoaking the recycled aggregates in acids significantly improves the properties of RA. Acid treated and silica fume impregnated recycled aggregate gave better concrete strength in the later age. The strength development of recycled aggregate concrete with treated RA was better than untreated RA. Abstract: Utilization of recycled aggregate (RA) from crushed concrete wastes as alternative to natural aggregate in construction industry solve the construction and demolition waste (C&DW) disposal problems and reduces the gap between the demand and supply. The adhered mortar affects the properties of RA to significant level. This paper has studied the characteristics of recycled aggregates retrieved from crushed old concrete obtained from demolished structures, and five different presoaking surface treatment method and silica fume impregnating method to improve the properties of the recycled aggregates and its effect on recycled aggregate concrete (RAC). From experimental results it was observed that after treatment there was a significant improvement in the physical and mechanical properties of RA because of adhered mortar removal. The compressive strength was also significantly improved by using treated RA in RAC. Hence it is concluded that these treatment methods can be effectively used for the recycled aggregates to improve its characteristics.